Odpowiedzi

Najlepsza Odpowiedź!
2009-10-27T16:34:32+01:00
L=2π*r
P=π*r²

a). 0,12 π mm
0,12π=2π*r
0,12=2r
r=0,06mm
P= π*(0,06)²=0,0036π

b). 4/9 π m ²
4/9π=π*r²
4/9=r²
r=2/3
l=2*2/3*π=3/2π=1½π m
1 5 1
2009-10-27T16:35:50+01:00
P = πr² Ob = 2πr

a) Ob = 0,12 π mm

2πr = 0,12π /:π
2r = 0,12 /:2
r = 0,6

P = πr²
P = 0,6π²
P = 0,036π mm

b) ⁴/₉ π m²

Ob = ⁴/₉ π m²
2πr = ⁴/₉ π /:π
2r = ⁴₉ /:2
r = ²/₉

P = ²/₉ π²
P = ⁴/₈₁ π m²

1 5 1
2009-10-27T16:39:25+01:00
A) Ob= 0,12 π mm
Ob= 2πr
prównujesz jedno do drugiego tzn. jedno równa się drugie:

2πr= 0,12 π mm./:π
2r= 0,12 mm./: 2
r= 0,06 mm.

P= πr²
P= π•(0,06mm)²
P= 0,0036•π
P= 0,0036π mm²

b) Ob= ⁴/₉π m²
Ob= 2πr (tak jak w poprzednim)

2πr= ⁴/₉π ²/:π
2r= ⁴/₉ /:2, lub /•¹/₂
r= ⁴/₁₈ m (skracasz)
r= ²/₉ m.

P= πr²
P= π•(²/₉)²
P= π•⁴/₈₁
P= ⁴/₈₁π m²
1 5 1